Pengaruh Free Cash Flow, Return On Assets, Total Assets Turnover Dan Sales Growth Terhadap Dividend Payout Ratio (Studi Empiris Pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Mohammad Alfan Syahroni; Maslichah Maslichah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2017)
ABSTRACTThis research is conducted with the aim of: 1) For Free Cash Flow, Return OnAssets, Total Assets Turnover And Sales Growth simultaneously against DividendPayout Ratio at LQ45 company in BEI. 2) For Free Cash Flow, Return On Assets,Total Assets Turnover And Sales Growth partially against Dividend Payout Ratio atLQ45 company in BEIThe population used in this study are all LQ45 companies listed on the IndonesiaStock Exchange (BEI) in 2013-2015. Sample selection using purposive sampling.Based on the criteria, obtained 19 companies that become samples in this study. Themethod used in this study using multiple linear regression method.Based on the results of the analysis can be put forward several conclusions asfollows: 1) F test results show that the variables Free Cash Flow, Return On Assets,Total Assets Turnover And Sales Growth simultaneously against the Dividend PayoutRatio. 2) The result of t test shows that for free cash flow variable has significanteffect but has negative relationship toward Dividend Payout Ratio. 3) Return onAssets variable partially has no effect on Dividend Payout Ratio. 4) Total AssetsTurnover partially has no effect on Dividend Payout Ratio. 5) Sales Growth partiallyhas no effect on Dividend Payout Ratio.